Montenegro : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Montenegro. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Montenegro's economy continues to grow at a moderate pace. The growth should continue over the medium term, boosted by the implementation of large investment projects, including the construction of the Bar-Boljare Highway. The IMF staff projects the economy to expand by 3 percent in 2017 and 2.75 percent in 2018, with planned fiscal consolidation acting as a moderate drag on growth. Conditions in the banking sector continue to strengthen, with improving asset quality and recovering credit growth. Nonperforming loans, however, remain elevated, and the sector appears to be over-banked, presenting a challenge for bank profitability.